Imagined economies : the sources of Russian regionalism - Herrera, Yoshiko M., 1970- (Cambridge studies in comparative politics., 2005)
This book analyzes the economic bases of regional sovereignty movements in the Russian Federation from 1990-1993. The book addresses the literature on both nationalism and political economy and provides a novel analytic framework for explaining the origin of economic interests and the development of sovereignty movements.